Development of STEM-Based PjBL Model Science Learning Tools to Train Middle School Students’ Creativity Through Flood Detection Alarm Project Taks - Indah Solichatin; Wahono Widodo; Munasir Munasir (IJORER : International Journal of Recent Educational Research, 2022)
The purpose of the research is to develop a STEM-based PjBL model of learning tools to train students' creativity through the Flood Detection Alarm project task. The research development design is a 4D model (Define, Design, Develop and Disseminate). Methods of collecting research data using validation, questionnaires, observation, assessment, and documentation.The validity of the learning device has an average score above the value of 3 (valid). The practicality of learning devices is in the very good category, obstacles that occur during learning can be resolved with several solutions so that learning can run smoothly as expected. The effectiveness of the learning tools is effective in terms of the creativity of the students, the average score is 87.6% (very creative) and the students' responses are the average score is 94% (positive). The conclusion that can be underlined from the results of this study is the development of science learning tools with the PjBL model with a STEM approach that is suitable for training students' creativity in making Flood Detection Alarm products on Dynamic Electricity material.